Environmental vices as ethical and anthropological roots of the environmental crisis - Dzwonkowska, Dominika (Studia Ecologiae et Bioethicae, 2020)
The root of environmental crisis is not only the failure to recognize the intrinsic value of the non-human world, but it can also be perceived as a failure in moral excellence and in the cultivation of virtue. The word “virtue” is an old-fashioned one, representing tradition and today we mostly associate it with academic discussion. However, the term is not only connected with traditional ethical reflection; nowadays, we can witness a revival of virtue discourse in environmental ethics, namely in environmental virtue ethics. The paper analyses the problem of cardinal virtue and vice, and tries to answer which vices are the most responsible for the environmental crisis. Thus the five crucial environmental vices are defined as egoism, greed, arrogance, ignorance and apathy.